Association of Socio-Demographics with Oral Para Functional Habits - Rubab Amjad, Abdul Haseeb, Zeenia Khan, Zahra Moeen, Hira Butt, Maria Jabbar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the association of sociodemographic factors with oral parafunctional habits. Methodology: A Cross-sectional descriptive study was conducted in College of Dentistry, Sharif Medical and Dental College, Lahore over a period of 5 months from July to November 2021. Data was collected using medical questionnaire and ten item personality inventory scale (TIPI). Results: The association of nail biting with gender (p=0.315), marital status (p=0.653), occupation (p=0.137) and education level (p=0.081) was not significant. Similar was the case for teeth grinding and gender (p=0.223), marital status (p=0.927), occupation (p=0.711) and education level (p=0.197). The association of teeth clenching habit with gender (p=0.174), marital status (p=1.000), occupation (p=0.349) and education level (p=0.362) was not significant. The association of the parafunctional habits of biting hard objects and chewing gum with sociodemographic factors was also not significant. Conclusion: It was seen that the majority of females, unmarried, unemployed individuals and those with tertiary level of education reported to have the habit of nail biting, teeth grinding and teeth clenching, biting on hard objects and chewing gum. Keywords: sociodemographic factors, nail biting, teeth clenching, teeth grinding, lip biting